Mode of Action of Cholera Toxin: Stabilization of Catecholamine-Sensitive Adenylate Cyclase in Turkey Erythrocytes - Field, Michael (1974)
Preincubating turkey erythrocytes with cholera toxin alters their adenylate cyclase (EC 4.6.1.1) system: basal activity, maximal epinephrine-stimulatable activity, and affinity of the enzyme reaction for epinephrine are all increased. Pretreatment of erythrocytes with choleragenoid prevents these changes. Cholera toxin does not alter [(3)H]epinephrine uptake by intact erythrocytes. The increase in epinephrine-stimulatable cyclase activity appears to occur at the expense of fluoride-stimulatable activity, which is decreased by the toxin. In lysates from both toxin-treated and control cells, maximally stimulating amounts of epinephrine and fluoride, when added in combination, have a nearly additive effect on cyclase activity. These observations suggest that the adenylate cyclase system of the turkey erythrocyte may exist in two interconvertible forms, one that is catecholamine-responsive but fluoride-insensitive, and another that is fluoride-sensitive but not coupled to catecholamine receptors. Cholera toxin appears to stabilize the enzyme in its hormone receptor-coupled form.